Female Migrant Labor in the Philippines: The Institutionalization of Traditional Gender Roles in the Name of Economic Development - Sabiha Iman Mohyuddin (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
This paper investigates the ways the Philippines’ government applies Filipino ideas of femininity and kinship in pushing Filipina women into becoming transnational migrants as a means of economic development. Given that remittance money sent back by migrants to the Philippines makes up nearly ten percent of the country’s GDP, and that over half of Filipino overseas migrants are female, the Filipino government is committed to maintaining and overseeing transnational migration. As a way to maintain economic stability, the Filipino government has utilized traditional conceptions of femininity, domesticity, and kinship that influence the procurement, recruitment processes of oversea migration, and the creation of policies that regulate Filipina transnational migration.
Keywords: migration; labor; Philippines; development; women & amp; labor